Euroscepticism and european foreign policy after maastricht: an assessment of the influence of european parliament members - Ada, Alper (My University, 2019)
2014 Avrupa seçimlerinden sonra, son anket verilerinin ışığında, Avrupa Parlamentosu üyelerinin seleflerinden daha fazla kutuplaştığı görülmektedir. Daha fazla Parlamento üyesi entegrasyon spektrumunda kendilerini önceki yıllardan daha karşıt ya da taraftar uçlarına yerleştirmiştir. Avrupa kuşkucu Parlamento üyeleri’nin varlığı, ana akım gruplar için azımsanamayacak siyasi yoğunlaşmalara ve ayrışmalara neden olmuştur. Entegrasyon yanlısı milletvekilleri, bu Avrupa kuşkucu akışa hitap etmek için sert bir şekilde yanıt vermek ya da tersine hareket ediyor gibi görünmektedirler. Buna ek olarak, dış politika ve ekonomik krizler bu fenomenin zeminini hazırlamışlardır. Böylece, Avrupa bütünleşmesi bir kez daha sorgulanır hale gelmiştir. Krizler daha fazla ayrışık duygulara yol açarken, gelecekteki dış politika entegrasyonunun Parlamenterler üzerindeki kurumsal kısıtlamalarla güvence altına alınmaya çalışıldığı görünmüştür. Hem Muhalif grupların hem de bireylerin fikirlerinin uzlaştığı tutarlı bir dış politika oluşumu zor görünmektedir. Bu nedenle, Avrupa Parlamentosu üyesi siyasi grupların yanı sıra bağımsız aktörler “düzensiz” bir muhalefet olarak güçlü bir şekilde lanse edilmektedir. Ancak, ana akım siyasi grup üyelerinin kendi aralarında daha fazla uzlaşma sağladığı görülmüştür. Bu tez, Avrupa Parlamentosu'nun önde gelen Parlamento üyeleri ve grupları ile Avrupa Birliği'nin dış politikası arasındaki ilişkiyi incelerken, aktörlerin Avrupa Parlamentosu'ndaki resmi veya gayri resmi demokratik kısıtlamalara maruz kaldıklarını sorgulamaktadır. Bu tez aynı zamanda Avrupa Parlamentosu'nun bugünkü zorluklarını yorumlayarak yaklaşan Avrupa seçimlerini anlama yolunu da açıyor. Tez, Avrupa kuşkucu parlamento üyelerinin resmi ve gayri resmi bir takım kurumsal kısıtlamalarla karşı karşıya oldukları ve dış politika alanında ‘yumuşak’ veya etkisiz bir rol oynadıkları sonucuna varmaktadır. Bu durum Avrupa kurumlarındaki demokrasi açığına, farklı oy verme davranışlarına, sosyalizasyona ve toplumsal inşacılığa atıfta bulunularak irdelenmiştir.

After 2014 European elections, the latest survey data indicate that MEPs (Members of the European Parliament) have been becoming more polarized within the European Parliament than its predecessors. More MEPs have been placing themselves at the ends of either a more anti- or pro-integration spectrum than previous years. The flow of Eurosceptic MEPs appear to cause rather intensification and division of policy fondness for mainstream ones. Pro-integrationist MEPs seemed whether to respond in a harsh way or in reverse to address this Eurosceptic stream. In addition to this, external political and economic crisis have played the integral part of this phenomenon. Thus, European integration was put into a question even further. While the crisis has comprised further Eurosceptic sentiments, it has been proved that future integration in foreign policy is tried to be secured via institutional constrains on MEPs and other Eurosceptic actors. It is hard for opposition groups or individuals to create coherent foreign policy formation in order to defend their ideas. Therefore, while Eurosceptic political groups as well as non-attached MEPs in the European Parliament have strongly emphasised as an ‘untidy’ opposition, pro-European actors from mainstream political groups seemed having more compromises among themselves. While this thesis probed the relationship between growing numbers of Eurosceptic MEPs and their foreign policy choices, it has inquired whether those actors are exposed to formal or informal democratic constraints within the European Parliament. The thesis also paves the way to understand upcoming European elections via today’s hardships in the European Parliament. The thesis concluded that Eurosceptic MEPs play ‘soft’ or inefficient role concerning foreign policy issues because they face some formal and informal institutional constraints in the EP. This situation has been examined with reference to the democratic deficit in European institutions, different voting behaviours, socialization process and social constructivism.
Keywords: Avrupa Parlamentosu; Avrupa seçimleri; Avrupa şüpheciliği; Dış Politika European Parliament; European elections; Euroscepticism; Foreign Policy; Identity; Kimlik; Social Constructivism; Toplumsal inşacılık